Evolution of protoplanetary disks including detailed chemistry and mineralogy - Gail, Hans-Peter; Tscharnuter, Werner M. (Reactive flows, diffusion and transport, 2007)
The earliest phase of evolution of planetary system is determined by the intimate coupling of a number of physical and chemical processes: turbulent hydrodynamic flows under the action of gravity, radiative transfer in a dusty gas, extensive mixing of material by large scale flows and turbulent duffusion, vaporization and condensation of ices and minerals, chemical reactions in the gas phase and at the surface of dust grains, and agglomeration of dust into planets. The project attempted to develop the first numerical model calculations which account for at least the most important ones of these processes in a consistent way. The chemistry and mineralogy in the planetary formation region of protoplanetary disks was investigated and the basic processes which have to be included in a numerical model were determined. Stationary and time dependent models for protoplanetary disks including the basic chemistry and mineralogy were constructed in different approximations in one and two space dimensions. These allow to determine the composition of the disk material which determines the raw material for planet formation. Preliminary comparison with observations of primordial material in comets and meteorites from the formation time of the solar system shows that the models already reproduce successfully some basic observational features.